Transmembrane protein 106C promotes the development of hepatocellular carcinoma. Issue 11 (9th February 2020) - Luo, Xi; Han, Gang; Lu, Renfei; Guan, Shaopei; Wang, Yifan; Ju, Linling; Chen, Lin; Shao, Jianguo; Bian, Zhaolian
Abstract: Several protein‐coding genes have been identified to play essential roles in cancer biology, and they are dysregulated in many tumors. Transmembrane protein 106C (TMEM106C) is differentially expressed in several human and porcine diseases; however, the expression and biological functions of TMEM106C in hepatocellular carcinoma (HCC) are not clear. In our study, we obtained paired tissue samples from patients undergoing resection for HCC and public databases, which were analyzed for TMEM106C expression using quantitative real‐time polymerase chain reaction (qRT‐PCR). We further conducted in vitro and in vivo experiments in HCC cell lines and nude mice, respectively, in which TMEM106C was overexpressed or knocked down. Cell‐Counting Kit‐8 and colony formation experiments were used to determine the influence of TMEM106C on cell proliferation, flow cytometric assays were used to detect the influence on cell cycle distribution and apoptosis, and transwell assays were used for detecting changes in cell migration and invasion. TMEM106C levels were significantly elevated in HCC tissues and cell lines from public databases and our collected specimens from patients. Moreover, higher TMEM106C expression levels predicted a poor prognosis in HCC patients in survival analysis. Overexpression of TMEM106C in HCC cells accelerated cell growth, migration, and invasion, but it inhibited cell apoptosis by targeting forkhead box O‐1 (FOXO1) and FOXO3. Conversely, TMEM106C knockdown impeded cell proliferation and metastasis, whereas it enhanced the rate of apoptosis. More important, knockdown of the expression of TMEM106C in HCC cells inhibited the growth of xenograft tumors in vivo. Collectively, these results suggest that TMEM106C acts as an oncogene and can serve as a potential therapeutic target for HCC in the future. Abstract : In our study, we used a series of gain‐ or loss‐function experiments to demonstrate that transmembrane protein 106C (TMEM106C) promotes proliferation and metastasis in hepatocellular carcinoma (HCC) and inhibits cell apoptosis. This is the first convincing report to demonstrate that TMEM106C is an oncogene in HCC. Further understanding of the underlying mechanisms of TMEM106C in the molecular etiology and progression of HCC will promote this therapeutic target against HCC.